Kebijakan Pemerintah Kabupaten Boyolali dalam Menekan Angka Buang Air Besar Sembarangan (BABS) - Annisa Dwi Novita Sari; Achmad Taufik (Journal of Politic and Government Studies, 2018)
The Stop of Defecation Free (Stop BABS) or Open Defecation Free (ODF) Program is one of the pillars of the Community-Based Total Sanitation Program (STBM) launched by the Ministry of Health of the Republic of Indonesia. The core of ODF District program activities is to reduce the number of environmental-based diseases such as diarrhea, cholera, and intestinal worms. The purpose of this study is to describe the implementation of policies used by Boyolali District Government in suppressing the number of defecation free, to know the difference of community behavior in Sawit Sub-district and Kemusu Sub-district and to know the factors causing the high of defecation free in both sub-district and to know the obstacle factors for the Boyolali District Government in suppressing the number of defecation free.The research method used is qualitative and quantitative descriptive approach with data collection technique that is observation, interview, questionnaire and documentation questionnaire. The informants in this research are Environmental Health Facilitator of Boyolali District, ODF District Facilitator, Movement of Health Cadre of Boyolali District, and Boyolali District Community.The result of the research shows that the implementation of Open Defecation Free (ODF) program is optimal. The implementation has been running optimally because it supported by the behavior of people who want to change the pattern of their life.Keywords: ODF District, Policy, The Number of Defecation Free